Financing Growth in the WAEMU Through the Regional Securities Market : Past Successes and Current Challenges - Diouf, Mame Astou (IMF Working Papers; Working Paper ;, 2012)
The West African Economic and Monetary Union (WAEMU) regional securities market saw increasing activity in the last decade, but still fell short of supplying sufficient long-term financing for growth-enhancing public and private investment projects. In addition to providing an institutional background, this paper studies recent developments and the determinants of interest rates on the market-using yield curve and principal component analyses. It also identifies challenges and prospective reforms that could help the region reap the full benefits of a more dynamic securities market and assesses the potential systemic risk the market may pose for the region's banking system.